(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
In this article, if we consider Uzbek folklore as an urgent problem of study, first of all, Uzbek folklore studies, its origin and influence on today’s educational process are reflected in this article. The study of Uzbek folklore is important for today’s time, because it shows the past of the Uzbek people, the extent to which our customs and traditions were formed in the past and to what extent they are being paid attention to now. we can see.